"It's been like a miracle": Low-income Arkansans and access to health care services following Medicaid reform - Traci H. Abraham PhD; Sacha A. McBain PhD; Anthony Goudie PhD; Teresa Hudson PharmD, PhD; Joseph W. Thompson MD, MPH (SAGE Publishing, 2020)
This article reports qualitative results from a mixed-methods evaluation of the Arkansas Health Care Independence Program. Qualitative data was collected using telephone interviews with 24 low-income Arkansans newly enrolled in Medicaid or a Qualified Health Plan in 2014. We used methods developed for rapid qualitative assessment to explore a range of general barriers and facilitators to accessing health care services. Secondary analysis guided by the most significant change technique aided in the construction of case summaries that permitted insights into participants' experiences of managing their health over time. Barriers to accessing health care services included treatment costs, beliefs and values related to health, limited health literacy, poor quality health care, provider stigma, and difficulties that made travel challenging. For 1 participant who was no longer eligible for Medicaid or a QHP, lacking health care coverage was also problematic. Facilitators included having health care coverage, life experiences that re-enforced the value of prevention, health literacy, and enhanced health care services. Low-income Arkansans experiences accessing health care elucidate access as multi-dimensional, involving not only the availability of affordable services, but treatment effectiveness and patient experiences interacting with providers and clinic staff. We use these findings to formulate recommendations for programs and policies aimed at further increasing access to high-quality health care as a strategy for reducing health disparities.